2006
DOI: 10.7589/0090-3558-42.3.712
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Visceral Coccidiosis in a Wild White-naped Crane (Grus vipio)

Abstract: ABSTRACT:Disseminated visceral coccidiosis (DVC) was unexpectedly recognized in a wild white-naped crane (Grus vipio) killed by phosphamidon insecticide. On gross pathologic examination, widely disseminated white nodules were found on the serosa of the proventriculus, gizzard, and intestine, as well as on the surface and in the parenchyma of liver, spleen, and cardiac muscle. Microscopically, asexual stages of a coccidia were observed in some nodules. However, the species of coccidia could not be determined be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…are known to be pathogenic in Sandhill Cranes (Carpenter, 1993), although no lesions were seen in these birds. Although DVC is a common pathogenic condition of cranes, especially chicks in captivity (Novilla and Carpenter, 2004;Kwon et al, 2006;Sarashina et al, 2006), both cases reported here appear incidental. All Whooping Cranes in the EMP were fed an artificial diet containing the coccidiostatic drug monensin from hatching until direct release at NNWR (5 mo of age) or departure from the CNWR pensite (10 mo of age).…”
Section: Discussionmentioning
confidence: 65%
“…are known to be pathogenic in Sandhill Cranes (Carpenter, 1993), although no lesions were seen in these birds. Although DVC is a common pathogenic condition of cranes, especially chicks in captivity (Novilla and Carpenter, 2004;Kwon et al, 2006;Sarashina et al, 2006), both cases reported here appear incidental. All Whooping Cranes in the EMP were fed an artificial diet containing the coccidiostatic drug monensin from hatching until direct release at NNWR (5 mo of age) or departure from the CNWR pensite (10 mo of age).…”
Section: Discussionmentioning
confidence: 65%
“…Chronic infections are characterized by granulomas disseminated throughout many organs [11]. DVC is an important cause of crane chick mortality in captivity [12, 14–16], and has also been described in captive adult cranes [17]. In one study, experimentally infected sandhill crane ( Grus canadensis ) chicks all developed granulomas, and 23.8% of wild sandhill cranes had granulomas at necropsy [18].…”
Section: Introductionmentioning
confidence: 99%
“…This disease has also been reported as a recurring disease in wild populations of sandhill cranes (Carpenter and others 1984) and in the non‐migratory Missisipi sandhill crane ( Grus canadensis pulla ) (Forrester and others 1978). Infection has been reported in wild cranes in Korea (Kwon and others 2006) and Japan (Matsubayashi and others 2005, Sarashina and others 2006) as well as in the USA, although few mortalities have been reported in these populations (Carpenter and others 1979, Forrester and Spalding 2003, Watanabe and others 2003). DVC has more recently been reported in a captive four‐month‐old white‐naped crane in Korea (Kim and others 2005).…”
mentioning
confidence: 99%